Organizational Development: A Tool for Nonprofit Organizations to Become Professional - Ferenc Farkas; Katalin Dobrai (International School for Social and Business Studies, 2013)
The paper is based on international research and on the ongoing research ofthe authors in the field of professionalization of nonprofit organizations. Deskresearch is supported by the analysis of the results of the pilot project of anorganizational development programme in Hungary. The findings of the empiricalresearch serve as a benchmark for the large sample research. Since thepaper gives insight over changes in the operational environment of nonprofitorganizations that are connected to their learning needs and chosen solutions,and brings practical evidence, it contributes to the current research ofprofessionalization of nonprofit sector organizations internationally.